Hybridization effects on wave packet dynamics in topological insulator thin films. (24th October 2017) - Yar, Abdullah; Naeem, Muhammad; Khan, Safi Ullah; Sabeeh, Kashif
Abstract: Theoretical study of electron wave packet dynamics in topological insulator (TI) thin films is presented. We have investigated real space trajectories and spin dynamics of electron wave packets in TI thin films. Our focus is on the role of hybridization between the electronic states of the two surfaces. This allows us to access the crossover regime of a thick film with no hybridization to a thin film with finite hybridization. We show that the electron wave packet undergoes side-jump motion in addition to zitterbewegung. The oscillation frequency of zitterbewegung can be tuned by the strength of hybridization, which in turn can be tuned by the thickness of the film. We find that the spin expectations also exhibit zitterbewegung tunable by hybridization. We also show that it is possible to obtain persistent zitterbewegung, oscillations which do not decay, in both the real space trajectories as well as spin dynamics. The zitterbewegung oscillation frequency in TI thin films falls in a parameter regime where it might be possible to observe these effects using present day experimental techniques.